LANGUAGE PREFERENCE OF BILINGUAL PRESCHOOL CHILDREN IN ARTICULATING WORD-OBJECT RELATIONSHIPS - Susyetina, Arida (IKIP Mataram, 2019)
This study attempts to focus on one factor of bilingual acquisition and language differentiation by exploring bilingual preschoolers’ language preference in articulating word-object relationships using concentrated descriptive and associative questions. Ten bilingual preschool children from middle-class families participated in the study. Pre-testing phase was conducted before the actual testing phase and the preschool teachers were consulted to confirm the data collection. These observations on general language bias as well as preferences developed by the males and females participants may have significant implications for language teaching that teachers shall carefully deliberate the kind of classroom culture they would like their learners to experience because strong language bias could possibly develop in language prejudice that may obstruct healthy bilingual development.